Does Treatment with Sodium-Glucose Cotransporter-2 Inhibitors Affect Adherence to International Society Criteria for Diabetic Ketoacidosis in Adult Patients with Type 2 Diabetes? A Retrospective Cohort Analysis - Aongus O’Brolchain; Joshua Maletsky; Ibrahim Mian; Serena Edwards (Journal of Diabetes Research)
Objective(s). Diabetic ketoacidosis (DKA) is a rare but well-known complication of sodium-glucose transporter inhibitor (SGLT2i) treatment in patients with type 2 diabetes. The physiological effects of SGLT2i are such that hyperglycaemia and ketonuria are no longer reliable diagnostic tools in patients treated with this class of medication. Diagnostic criteria for DKA varies between major society guidelines. The Joint British Diabetes Society (JBDS) and American Association of Clinical Endocrinology/American College of Endocrinology (AACE/ACE) have recently made changes to their diagnostic criteria to account for the effects of SGTL2i. This study sought to investigate whether treatment with SGLT2i might result in overdiagnosis of DKA and less adherence to the international diagnostic guidelines in hospitalised patients with type 2 diabetes treated with SGLT2i. Additionally, the demographics and clinical characteristics of patients with type 2 diabetes presenting with DKA were compared based on their treatment with SGLT2i at the time of diagnosis. Design. Retrospective observational study. Setting. Inpatients at two teaching hospitals in Queensland, Australia. Primary Outcome Measure(s). The number of patients meeting the Joint British Diabetes Society (JBDS) and American Association of Clinical Endocrinology/American College of Endocrinology (AACE/ACE) diagnostic criteria for DKA. Patients were divided into two groups by treatment with SGLT2i at the time of diagnosis. Participants. Adult patients (>18 years old) with type 2 diabetes diagnosed with DKA from April 2015 to January 2022. Patients without type 2 diabetes were excluded. Results. One hundred and sixty-five patients were included in this study—comprising 94 patients in the SGLT2i cohort and 70 in the non-SGLT2i cohort. A significantly smaller proportion of patients in the SGLT2i vs. non-SGLT2i cohorts met both JBDS (56% vs. 72%, p=0.035) and AACE/ACE (63% vs. 82%, p=0.009) criteria for diagnosis of DKA. Conclusion. Patients with type 2 diabetes treated with SGLT2i may be more likely to be diagnosed with DKA despite not meeting the criteria. Despite recent adjustments to account the physiological effects of SGLT2i, significant variation in criteria between major society guidelines presents ongoing challenges to clinicians. The proportion of patients diagnosed using both JDBS and AACE/ACE were comparable, suggesting a reasonable degree of agreement.